2006
DOI: 10.1002/eji.200635943
|View full text |Cite
|
Sign up to set email alerts
|

cIAP‐2 and survivin contribute to cytokine‐mediated delayed eosinophil apoptosis

Abstract: The exact molecular mechanisms leading to delayed apoptosis, a phenomenon frequently observed in eosinophil inflammatory responses, remain largely unknown. Here, we show that cultured eosinophils purified from blood of hypereosinophilic syndrome (HES) patients exhibit delayed spontaneous death and relative resistance towards ceramide-but not CD95-mediated death. The subsequent investigation of members of the inhibitor of apoptosis (IAP) family revealed that HES but not normal eosinophils expressed high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…The proapoptotic BH3-only Bcl-2 homologue Bid is highly expressed in human eosinophils and gets activated by withdrawal of IL-5 or at least partially by Fas-mediated signals (32). It was further demonstrated that inhibitor of apoptosis proteins cIAP-2 and survivin were up-regulated in eosinophils by IL-5, IL-3, and GM-CSF and inhibited caspase-3 activation via the mitochondrial pathway but not via the Fas pathway (33). Although IL-5 has been shown to prolong eosinophil survival ex vivo, clinical trials aimed at reducing eosinophil counts in allergic asthma patients by anti-IL-5 therapy were rather unsuccessful.…”
Section: Discussionmentioning
confidence: 98%
“…The proapoptotic BH3-only Bcl-2 homologue Bid is highly expressed in human eosinophils and gets activated by withdrawal of IL-5 or at least partially by Fas-mediated signals (32). It was further demonstrated that inhibitor of apoptosis proteins cIAP-2 and survivin were up-regulated in eosinophils by IL-5, IL-3, and GM-CSF and inhibited caspase-3 activation via the mitochondrial pathway but not via the Fas pathway (33). Although IL-5 has been shown to prolong eosinophil survival ex vivo, clinical trials aimed at reducing eosinophil counts in allergic asthma patients by anti-IL-5 therapy were rather unsuccessful.…”
Section: Discussionmentioning
confidence: 98%
“…Prolonged tissue survival has also been suggested to contribute to the accumulation of human eosinophils in nasal polyps (24), atopic dermatitis (25), bronchial asthma (26), and patients with eosinophilia (27,28; for a recent review on regulation of eosinophil apoptosis, see Ref. 29).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Modulation of neutrophil and eosinophil apoptosis mediated by these cytokines has been suggested to rely on the up-regulation of antiapoptotic proteins of the Bcl-2 family, such as Bcl-2, Bcl-X L , Mcl-1 and A1, [7][8][9] as well as IAP family proteins. [10][11][12] With regards to signaling pathways, Janus kinase (JAK)/signal transducer and activator of transcription 3 and 5 (Stat3/Stat5), phosphatidylinositol 3-kinase (PI3-kinase), as well as p38-mitogen-activated protein kinase (MAPK) have been implicated in the regulation of neutrophil and eosinophil apoptosis by GM-CSF, IL-5, and IL-3. [13][14][15][16][17][18][19] Although previous studies showed that IL-3 prolongs the life span of basophils, 5,6 there is a complete lack of knowledge about the proteins and the mechanisms that regulate spontaneous and cytokineenhanced survival of basophils.…”
Section: Introductionmentioning
confidence: 99%